Using the structural diversity of RNA: protein interfaces to selectively target RNA with small molecules in cells: methods and perspectives - Li, Aixiao; Bouhss, Ahmed; Clément, Marie-Jeanne; Bauvais, Cyril; Taylor, J. Paul; Bollot, Guillaume; Pastré, David (Frontiers in Molecular Biosciences, 2023)
In recent years, RNA has gained traction both as a therapeutic molecule and as a therapeutic target in several human pathologies. In this review, we consider the approach of targeting RNA using small molecules for both research and therapeutic purposes. Given the primary challenge presented by the low structural diversity of RNA, we discuss the potential for targeting RNA:protein interactions to enhance the structural and sequence specificity of drug candidates.We review available tools and inherent challenges in this approach, ranging from adapted bioinformatics tools to in vitro and cellular high-throughput screening and functional analysis.We further consider two critical steps in targeting RNA:protein interactions: first, the integration of in silico and structural analyses to improve the efficacy of molecules by identifying scaffolds with high affinity, and second, increasing the likelihood of identifying on-target compounds in cells through a combination of high-throughput approaches and functional assays. We anticipate that the development of a new class of molecules targeting RNA:protein interactions to prevent physio-pathological mechanisms could significantly expand the arsenal of effective therapeutic compounds.